Expression of cyclooxygenase-1 and 2 in chronic tonsillitis - Dilek Fatma; Sahin Onder; Tokyol Cigdem; Mazlum Mustafa; Aycicek Abdullah (Wolters Kluwer Medknow Publications, 2010)
Objectives: Prostaglandins are critical mediators of inflammation and affect both humoral and cell-mediated immune responses. Recent findings show that T and B cells express COX-2 upon activation. The purpose of this study is to investigate the potential occurrence of COX-1 and COX-2 immunoreactivity in cases of chronic tonsillitis and to determine the sites of their expression. In addition, their expression in adult patients is compared with that in child patients. Materials and Methods: Immunohistochemical techniques were used to evaluate the expression of the enzymes COX-1 and COX-2, in chronic tonsillitis tissue specimens from adults (n = 15) and children (n = 15). Results: There was no staining in surface epithelium or reticulated crypt epithelium. COX-1 and COX-2 expressions were observed mainly in the intraepithelial lymphoid cells in reticulated crypt epithelium and subepithelial cells. Also, COX-1 and COX-2 stained cells were found in the germinal center. There was no difference of the expressions of COX-1 and COX-2 among adults and children. The only significant difference noted between the adults and children was that, the adults had rich subepithelial plasma cells. Conclusion: Activated B and T cells express COX-1 and COX-2 in paraffin-embedded tissue sections of chronic tonsillitis. Further studies need to be performed to elucidate expression of COX enzymes and their immunologic role in tonsil diseases. They will play an important role in the treatment of chronic tonsillitis. Additional studies are warranted to study the effects of NSAIDs and selective COX-2 inhibitors in chronic tonsillitis